Стратифікація концепту - Яремко, Я.П. (Мовознавство, 2009)
У статті проводиться стратифікація концепту у зв’язку зі структурою комунікативної
особистості. З’ясовуються особливості вербалізації концепту, причини її відсутності. The article examines the stratification of the concept in connection with the structure of the communicative
personality. The peculiarities of the concept verbalization and the reasons of its absence
are made clear.